PENGARUH PENGAPLIKASIAN VARIASI PERANGKAP TERHADAP JUMLAH LALAT TERPERANGKAP DI TEMPAT PENJUALAN IKAN PASAR TAMBAK LOROK KOTA SEMARANG - Choirul Azizah; Retno Hestiningsih; Sri Yuliawati; Moh Arie Wuryanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
The density of flies at the fish sales of Tambak Lorok Market, Semarang City is included in the high category with a density number of 9.35. Based on observation showed that no control has been carried out to reduce the fly population at the fish sales of Tambak Lorok Market, Semarang City. The way to control fly population is to use fly traps. The aim of study was to analyze the effect of trap variations on the number of trapped flies at the fish sales of Tambak Lorok Market, Semarang City. The type of research used was observasional with a cross sectional study design. The samples in this study were flies trapped in various types of traps (sticky trap, fly trap, bottle trap, tree flies) installed at the fish sales of Tambak Lorok Market. The result of the Kruskal Wallis test showed a significance value of 0.000 (α < 0.05) so that there were differences in the variation of traps on the number of trapped flies. In conclusion, the fly trap that traps the most flies is the sticky trap. It is hoped that fish traders can carry out fly control to reduce fly density.